Sudden cardiac death: epidemiology and risk factors - Adabag, A. Selcuk (Nat Rev Cardiol, 2010)
Sudden cardiac death (SCD) is an important public-health problem with multiple etiologies, risk factors, and changing temporal trends. Substantial progress has been made over the past few decades in identifying markers that confer increased SCD risk at the population level. However, the quest for predicting the high-risk individual who could be a candidate for an implantable cardioverter-defibrillator, or other therapy, continues. In this article, we review the incidence, temporal trends, and triggers of SCD, and its demographic, clinical, and genetic risk factors. We also discuss the available evidence supporting the use of public-access defibrillators.